2023
DOI: 10.3389/fpsyt.2023.1150374
|View full text |Cite
|
Sign up to set email alerts
|

Association of fear of COVID-19 and resilience with psychological distress among health care workers in hospitals responding to COVID-19: analysis of a cross-sectional study

Abstract: BackgroundIt remains unclear how fear of COVID-19 and resilience are related to psychological distress based on occupations among healthcare workers (HCWs) in hospitals treating patients with COVID-19. We conducted a survey on the mental health of HCWs during the COVID-19 pandemic to determine the relationship between factors such as fear of COVID-19 and resilience as well as mental distress in each occupation of HCWs.MethodsWe conducted a web-based survey among HCWs at seven hospitals treating COVID-19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(53 reference statements)
0
5
1
Order By: Relevance
“…Regarding psychological distress, the prevalence reported in this study, 15.2%, appears to be lower than that reported in previous studies carried out during the COVID‐19 pandemic, although a direct comparison is difficult because of the differences in the study design, target population and assessment methods 1–3 . The analytic sample in the present study was limited to doctors; however, doctors might be less susceptible to psychological distress than other healthcare workers 29–31 . In addition, the doctors in this study were not necessarily involved in the direct care of COVID‐19 patients; this might have made the prevalence of psychological distress lower, because directly engaging in COVID‐19 care has been associated with a higher prevalence of depression among healthcare workers 3 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Regarding psychological distress, the prevalence reported in this study, 15.2%, appears to be lower than that reported in previous studies carried out during the COVID‐19 pandemic, although a direct comparison is difficult because of the differences in the study design, target population and assessment methods 1–3 . The analytic sample in the present study was limited to doctors; however, doctors might be less susceptible to psychological distress than other healthcare workers 29–31 . In addition, the doctors in this study were not necessarily involved in the direct care of COVID‐19 patients; this might have made the prevalence of psychological distress lower, because directly engaging in COVID‐19 care has been associated with a higher prevalence of depression among healthcare workers 3 .…”
Section: Discussioncontrasting
confidence: 56%
“…Generalization to doctors in other specialties or other healthcare occupations should be done with caution and attention to the differences in occupational characteristics. Previous studies in Japan reported that doctors have a low fear of COVID‐19 and higher resilience than other healthcare professionals 30,31 . Finally, as the study was observational in nature, the findings might be confounded by unobserved or unmeasured variables.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between fear and psychological distress, particularly in the context of COVID‐19, has indeed been extensively studied. 31 , 33 , 34 Research has consistently shown that fear is a significant precursor for psychological distress, and this association has been observed in various populations, including healthcare workers. For instance, Ghozy et al in their cross‐sectional analyses from 14 countries reported that healthcare workers who experienced higher levels of fear related to COVID‐19 also exhibited higher levels of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fear and psychological distress, particularly in the context of COVID‐19, has indeed been extensively studied 31,33,34 . Research has consistently shown that fear is a significant precursor for psychological distress, and this association has been observed in various populations, including healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, building psychological resilience emerged as an essential focus in response to these challenges, as it may serve as a protective factor against the risk of developing burnout and its negative consequences on individuals and the health care system [ 14 , 16 ]. Higher personal resilience was found to be associated with lower stress levels and lower levels of anxiety, COVID-19 related fear, depression, fatigue, and sleep disturbances during the COVID-19 pandemic [ 17 19 ]. Besides the well-known positive effects of resilience on physicians’ well-being, there is some evidence suggesting that it could also protect against detrimental effects of a health care crisis by maintaining a high level of health care quality.…”
Section: Introductionmentioning
confidence: 99%